DETECTION OF PRECLINICAL AND PRODROMAL ALZHEIMER'S DISEASE USING A MULTIDISEASE DIAGNOSTIC PLATFORM. (20th December 2022) - DeMarshall, Cassandra; Viviano, Jeffrey; Emrani, Sheina; Godsey, George; Sarkar, Abhirup; Belinka, Benjamin; Libon, David; Nagele, Robert
Abstract: AD-related pathological changes begin in the brain long before symptoms emerge. In the present study, we demonstrate the utility of a panel of AD-related autoantibodies capable of detecting AD at the earliest points along the AD continuum, including preclinical AD, years before the onset of symptoms, and prodromal AD (mild cognitive impairment, MCI). Using a customized panel of AD-specific autoantibody biomarkers and Luminex xMAP® technology, sera from ADNI subjects with preclinical AD or MCI were screened to demonstrate preclinical and prodromal AD detection. A panel of eight autoantibodies with increased titer in MCI and preclinical AD relative to controls was evaluated using Random Forest and Receiver Characteristic Operating curves for their ability to distinguish diseased subjects from age- and sex-matched controls, as well as from individuals with other neurodegenerative and non-neurodegenerative diseases. Results showed that this panel of biomarkers was capable of differentiating patients with MCI from age- and sex-matched controls with high overall accuracy, sensitivity, and specificity. These biomarkers also identified cognitively normal subjects who later converted to MCI and AD. Furthermore, this autoantibody biomarker panel distinguished MCI and preclinical AD subjects from Parkinson's disease and breast cancer subjects, demonstrating excellent disease specificity. Results demonstrate the utility of our blood-based autoantibody biomarker panel as an accurate, non-invasive, and inexpensive diagnostic screener, not only for the detection of prodromal AD, but also the earlier, preclinical stages of AD pathology. This multi-disease diagnostic platform has been demonstrated to be useful for multiple neurodegenerative diseases including AD, Parkinson's disease and Multiple Sclerosis.